A novel cell surface polysaccharide in Pseudomonas putida WCS358, which shares characteristics with Escherichia coli K antigens, is not involved in root colonization. - de Weger, L A (1996)
Previously we have shown that flagella and the O-specific polysaccharide of lipopolysaccharide play a role in colonization of the potato root by plant growth-promoting Pseudomonas strains WCS374 and WCS358. In this paper, we describe a novel cell surface-exposed structure in Pseudomonas putida WCS358 examined with a specific monoclonal antibody. This cell surface structure appeared to be a polysaccharide, which was accessible to the monoclonal antibody at the outer cell surface. Further study revealed that it does not contain 2-keto-3-deoxyoctonate, heptose, or lipid A, indicating that it is not a second type of lipopolysaccharide. Instead, the polysaccharide shared some characteristics with K antigen described for Escherichia coli. From a series of 49 different soil bacteria tested, only one other potato plant growth-promoting Pseudomonas strain reacted positively with the monoclonal antibody. Mutant cells lacking the novel antigen were efficiently isolated by an enrichment method involving magnetic antibodies. Mutant strains defective in the novel antigen contained normal lipopolysaccharide. One of these mutants was affected in neither its ability to adhere to sterile potato root pieces nor its ability to colonize potato roots. We conclude that the bacterial cell surface of P. putida WCS358 contains at least two different polysaccharide structures. These are the O-specific polysaccharide of lipopolysaccharide, which is relevant for potato root colonization, and the novel polysaccharide, which is not involved in adhesion to or colonization of the potato root.